2017
DOI: 10.14423/smj.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Shock Index for Risk Stratification in Patients with Acute Upper Gastrointestinal Bleeding

Abstract: The shock index is a good tool to identify patients with the potential for short-term adverse outcomes when they present with UGIB. It performs as well as other risk-scoring tools for GI bleeding and has the potential for serial use during hospitalization to identify changes in the clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
1
20
0
2
Order By: Relevance
“…In a study among healthy participants with blood loss of 450 ml, the SI was substantially increased whereas the HR and SBP remained within the normal ranges [ 44 ]. Classification of patients by an SI > 0.7 can preferentially select patients with adverse short-term outcomes from among those with upper gastrointestinal bleeding [ 45 ]. With SI above 0.9, the risk for trauma patients requiring massive transfusion rises substantially [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study among healthy participants with blood loss of 450 ml, the SI was substantially increased whereas the HR and SBP remained within the normal ranges [ 44 ]. Classification of patients by an SI > 0.7 can preferentially select patients with adverse short-term outcomes from among those with upper gastrointestinal bleeding [ 45 ]. With SI above 0.9, the risk for trauma patients requiring massive transfusion rises substantially [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SI can provide a comprehensive assessment of cardiovascular status and can be used to estimate the amount of blood loss and degree of shock (normal range: 0.5 to 0.7) [7]. A study by Rassameehiran et al showed that the SI was a good tool to identify patients with the potential for short-term adverse outcomes when they presented with upper gastrointestinal bleeding, and the SI was performed, as well as other risk-scoring tools, for gastrointestinal bleeding [22]. In this study, it was determined that the GBSs of patients with PUB were positively correlated with the SI, i.e., the higher the SI, the higher the GBS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are limited data on the use of the Shock Index in upper GI bleeding. Two small retrospective studies suggested that the Shock Index correlates with angiographic visualisation of bleeding, and that a Shock Index of >0.7 predicts need for endoscopic therapy and worse outcomes . Another retrospective study suggested that a Shock index >1.0 identifies patients at higher risk of hyperlactaemia and 28‐day mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Two small retrospective studies suggested that the Shock Index correlates with angiographic visualisation of bleeding, and that a Shock Index of >0.7 predicts need for endoscopic therapy and worse outcomes. 7,8 Another retrospective study suggested that a Shock index >1.0 identifies patients at higher risk of hyperlactaemia and 28-day mortality. 5 A prospective study described a simplified scoring system incorporating the Shock Index and found this to be comparable to the GBS in predicting high-risk endoscopic stigmata, re-bleeding and 30-day bleeding-related mortality.…”
Section: Introductionmentioning
confidence: 99%